Nilai Kebudayaan Tradisi Pendalungan dalam Kesenian Can- Macanan Kadhuk dalam Pengembangan Tradisi Budaya Jember - Nour Ainun Nisa; Muhammad Fadhlillah Akbar; Muhammad Rafi Kurniawan; Surya Rizki Mubarok (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This theory explains the existence of traditional pendalungan culture in the traditional culture of the Jember Regency area in the progress of modern arts and culture in passing on arts and culture education regarding can macanan kadhuk and his art can entertain arts and culture and also as a relative preference that a person has in dealing with and in participation in the larger community along with other ethnocultural groups. Schematically, the concept described in the Strategy as explained in the scheme above has different names depending on the ethnocultural group: whether the ethnocultural group is dominant or non-dominant. From the point of view of the non-dominant group (left), assimilation occurs when someone does not want to maintain their cultural identity and seeks daily interaction with other cultures. The opposite is a separation strategy. A separation strategy occurs when someone lives up to the values ​​of their original culture and at the same time avoids interacting with others. Nevertheless, when measures of preferences and behavior are both included in an assessment of how a society is acculturating, there is usually one pattern that indicates a consistent strategy.